Honduras : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
The paper reports the progress of the Honduran poverty reduction strategy program, projects, and policy measures. The report provides details on the organization and results of the consultation process, and analyzes the macroeconomic framework for the poverty reduction strategy. An overview of the poverty situation and the performance of the poverty-related economic and social indicators are also discussed. Finally, the adjustment of some poverty reduction strategy program goals and budget is presented. The strategy also proposes a series of policy measures.